Hydrogen’s effect on the shape memory effect of TiNi alloy single crystals - Kireeva, Irina V. физик; Chumlyakov, Yuri I.; Yakovleva, Liya P.; Vyrodova, Anna V. (Metals)
Hydrogen’s effect on the shape memory effect (SME) of [117]-oriented Ti49.7-Ni50.3 (at.%) alloy single crystals, with a B2–B190 martensitic transformation (MT), was studied after being electrolytically hydrogenated at a current density of 1500 A/m2 for 3 h at room temperature under isobaric tensile deformation. It was shown that, under the used hydrogenation regime, hydrogen was in a solid solution and lowered the elastic modulus of B190 martensite. The hydrogen in a solid solution increased (i) the yield strength 0.1 of the initial B2 phase by 100 MPa at Md temperature, (ii) the 0.1 of the stress-induced B2–B190 MT by 25 MPa at Ms temperature, and (iii) the plasticity of B190 martensite relative to the hydrogen-free crystals. At the same level of external stresses, the SME in the hydrogenated crystals was greater than that in hydrogen-free crystals. At external tensile stresses ex = 200 MPa, the SME was 4.4 0.2% in the hydrogenated crystals and 1.8 0.2% without hydrogen. Hydrogen initiated a two-way SME of 0.5 0.2% at ex = 0 MPa, which was absent in the hydrogen-free crystals. The physical reasons leading to an increase in the SME upon hydrogenation are discussed.